CHARACTERISTICS OF TRADITIONAL FOOD PRODUCTS AS A PREDICTOR OF CONSUMPTION IN HOSPITALITY - ON THE EXAMPLE OF SELECTED AREAS IN VOJVODINA - Stošić, Tamara; Šmugović, Stefan; Ivanović, Velibor; Kalenjuk Pivarski, Bojana (The Business of Tourism, 2022)
Traditional food products are an important part of catering and touristic offer. They have an impact on the representation of certain country or region to the consumers. Improvement and increasing of traditional food products consumption and their availability in catering establishments, can have multiple effect on number of other industries, and mostly on producers who belong to small or medium group producers. The topic of this paper consists of traditional food products, i.e. the importance of their characteristics as seen from the point of view of managers in catering establishments in Srem and Northern Bačka.The main task is to present their attitudes towards quality of traditional products (market, production and technical) which affect the purchase decision. The main aim of this paper is to collect data about traditional food products which are used in meal preparation in catering establishments in the area and whose traits are essential for their choice.
Keywords: traditional product, food, gastronomy, hospitality, Vojvodina, Srem, Bačka